Distress and worry as mediators in the relationship between psychosocial risks and upper body musculoskeletal complaints in highly automated manufacturing. Issue 8 (3rd August 2018) - Wixted, Fiona; Shevlin, Mark; O'Sullivan, Leonard W.
Abstract: As a result of changes in manufacturing including an upward trend in automation and the advent of the fourth industrial revolution, the requirement for supervisory monitoring and consequently, cognitive demand has increased in automated manufacturing. The incidence of musculoskeletal disorders has also increased in the manufacturing sector. A model was developed based on survey data to test if distress and worry mediate the relationship between psychosocial factors (job control, cognitive demand, social isolation and skill discretion), stress states and symptoms of upper body musculoskeletal disorders in highly automated manufacturing companies ( n  = 235). These constructs facilitated the development of a statistically significant model (RMSEA 0.057, TLI 0.924, CFI 0.935). Cognitive demand was shown to be related to higher distress in employees, and distress to a higher incidence of self-reported shoulder and lower back symptoms. The mediation model incorporating stress states (distress, worry) as mediators is a novel approach in linking psychosocial risks to musculoskeletal disorders. Practitioners' Summary With little requirement for physical work in many modern automated manufacturing workplaces, there is often minimal management focus on Work-Related Musculoskeletal Disorders (WRMSDs) as important occupational health problems. Our model provides evidence that psychosocial factors are important risk factors in symptoms of WRMSD and should be managed.